1993
DOI: 10.1128/jb.175.4.941-951.1993
|View full text |Cite
|
Sign up to set email alerts
|

Participation of RAP1 protein in expression of the Saccharomyces cerevisiae arginase (CAR1) gene

Abstract: Regulated expression of the inducible arginase (CARl) gene of Saccharomyces cerevisiae has been shown to require (2, 6, 19-21, 27b). However, it was recently shown that only arginine transport is NCR sensitive; the apparent NCR sensitivity of CARl expression is in reality NCR-sensitive inducer exclusion (7).The CAR1 upstream regulatory region contains four discrete cis-acting elements: two inducer-independent upstream activation sequences (UASs), UASCl and UASC2; an inducer-dependent UAS, UAS,; and an upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The arbitrarily defined UAS CI and UAS CII regions supported constitutive reporter gene expression when cloned into a heterologous expression vector (43,44,46). Genetic and in vitro biochemical studies demonstrated the UAS C regions potentially to contain two Abf1p-binding sites (44) and five Rap1p-binding sites (46).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The arbitrarily defined UAS CI and UAS CII regions supported constitutive reporter gene expression when cloned into a heterologous expression vector (43,44,46). Genetic and in vitro biochemical studies demonstrated the UAS C regions potentially to contain two Abf1p-binding sites (44) and five Rap1p-binding sites (46).…”
mentioning
confidence: 99%
“…The arbitrarily defined UAS CI and UAS CII regions supported constitutive reporter gene expression when cloned into a heterologous expression vector (43,44,46). Genetic and in vitro biochemical studies demonstrated the UAS C regions potentially to contain two Abf1p-binding sites (44) and five Rap1p-binding sites (46). However, the degrees to which individual sites were required for the DNA fragments containing them to support high-level ␤-galactosidase production when cloned into a CYC1-lacZ expression vector varied (44,46).…”
mentioning
confidence: 99%
“…In addition to the three 27-bp UAS1 elements described in this article, a further nine specific protein-binding sites have been previously reported to be present in the 5'-flanking region of CARI (Fig. 11) (12,13). They facilitate relation of the earlier work to that described in this article.…”
Section: Discussionmentioning
confidence: 50%
“…According to this model, the negative action of the strong URSI element balances the positive action of the strong, constitutively functioning UASCl and UASc2 elements (11)(12)(13)(14)(15). The balance is then tipped in the direction of expression when arginine is present, or quiescence when it is not, by operation of the inducer-dependent UASJ element (11)(12)(13)(14)(15).…”
Section: Cari (Arginase) Gene Expression In Saccharomyces Cere-mentioning
confidence: 99%
See 1 more Smart Citation